Zuranolone for treatment of major depressive disorder: a systematic review and meta-analysis - Ahmad, Abdullah; Awan, Abdul Rafeh; Nadeem, Natasha; Javed, Aamir Shahid; Farooqi, Mobeen; Daniyal, Muhammed; Mumtaz, Hassan (Frontiers in Neuroscience, 2024)
Background:Current treatment modalities for Major Depressive Disorder have variable efficacies and a variety of side effects.To amend this, many trials for short term, well tolerated monotherapies are underway. One such option is Zuranolone (SAGE-217),which is a recent FDA approved antidepressant for Post Partum depression(PPD) and is undergoing clinical trials for major depressive disorder (MDD) and essential tremors (ET).Objectives: Pool currently available data that compare Zuranolone to Placebo for the treatment of Major Depressive Disorder and evaluate its efficacy and safety profile.We retrieved data from PUBMED and SCOPUS from inception to July 2023. We included articles comparing Zuranolone or SAGE 217 with placebo in patients suffering from Major Depressive Disorder.Review Manager 5.4 was used to analyse the outcomes including changes in the Hamilton Depression Rating Scale (HAM-D), Hamilton Anxiety Rating Scale (HAM-A) and Montgomery-Åsberg Depression Rating Scale(MADRS) scores from baseline as well as any treatment emergent adverse events (TEAEs) and severe adverse events.Our review analysed 4 trials and the data of 1357 patients. Patients treated with Zuranolone indicated a statistically significant effect in the change from baseline in HAM-D score (P=0.0009; MD [95% CI]: -2.03 [-3.23, -0.84]) as well as in MADRS score (P=0.02; MD [95% CI]: -2.30[-4.31, -0.30]) and HAM-A score (P=0.03; MD [95% CI]: -1.41 [-2.70, -0.11]) on 15th day when compared to the Placebo group.Zuranolone was also significantly associated with a higher response rate (P=0.0008; OR[95% CI]:1. 63[1.14, 2.35]) and higher remission rate(P=0.03; OR[95% CI]:1.65[1.05, 2.59]) when compared with the placebo. As for safety, Zuranolone was significantly associated with atleast 1 TEAE (P=0.006; RR[95% CI]: 1.14[1.04, 1.24]) but an insignificant association with side effects that lead to drug discontinuation (P=0.70; RR[95% CI]: 1.18[0.51, 2.76]) and serious adverse events (P=0.48; RR[95% CI]: 1.46 [0.52, 4.10]) when compared with placebo.Zuranolone is an effective and safe drug for short course major depressive disorder monotherapy. It shows results in 14 days (compared to 2-4 weeks that SSRI's take) and has antianxiolytic effects as well. However, only 4 trials have been used for the analysis and the sample size was small. The trials reviewed also cannot determine the long-term effects of the drug.